The Effect of Using Different Types of Flour on Water Content, Water Activity, Water Holding Capacity, Fat Content, Cholesterol, and Color of Chicken Liver Meatballs - Maulida Aina Salsabila; Vivi Kartika Putri; Amertaningtyas, Dedes; Saleha, Rischa (Jurnal Ilmu dan Teknologi Hasil Ternak, 2024)
Meatball is a processed meat products made with a mix of ground meat, flour, and spices. The ingredients for making meatballs can be substituted by using internal organs of livestock, such as chicken liver meatballs. This research objective measured the effect of different types of flour (tapioca flour, sago flour, and maizena flour) in chicken liver meatballs to measure the physical qualities (water content, water activity, water holding capacity, color) and chemical qualities (fat content and cholesterol). The material used in this research were chicken liver, tapioca flour, sago flour, maizena flour, salt, pepper, sugar, fried shallots, garlic, albumin, and ice. The method used in this research was experimental and counted with a Randomized Block Design (RBD) with 3 treatments and 6 replications. T1: 26 % tapioca flour with 250 g chicken liver, T2: 26 % sago flour with 250 g chicken liver, and T3: 26 % maizena flour with 250 g chicken liver. The variables were fat content, cholesterol, and color. The result showed that average of water content on each flour was T1 61.65±0.49 %, T2 63.18±0.44 %, and T3 60.56±1.15 %. Water activity was T1 0.9427±0.0030, T2 0.9428±0.0070, and T3 0.9375±0.0036. WHC (Water Holding Capacity) was T1 49.38±1.21 %; T2 48.28±1.55 %, and T3 52.68±1.08 %. Fat content was T1 11.54±0.88 %, T2 11.33±0.66 %, and T3 11.01±0.76 %. Cholesterol level was T1 19.16±1.01 mg/100g, T2: 18,54±1.32 mg/100g, and T3 18.10±0.72 mg/100g. Color was T1 46.01±0.65, T2 43.67±1.13, and T3 43.09±2.15. This research concluded that the effect of three types of flour (tapioca, sago, and maizena) addition were highly significanly effect (P<0.01) on water content, water holding capacity, color L*, color a*, color b* and significanly effect (P<0.05) on water activity, but were not significanly effect (P>0.05) on fat content, and cholesterol level. Research can be continued with the use of tapioca flour, sago flour, and maizena flour in meatball products from other livestock livers with different variables